STRATEGI PEMBERDAYAAN PEREMPUAN MELALUI KELOMPOK WANITA NELAYAN FATIMAH AZZARAH KOTA MAKASSAR - Dewi Reca Litha; A Octamaya Tenri Awaru; Nur Aulia; Syahputri Intan Muqmi; Ahry Ramadhani (Social Landscape Journal, 2023)
This study aims to explore women's empowerment strategies and inhibiting factors as well as ways to overcome all inhibiting factors. Methodologically, this research is a descriptive-qualitative type with Husserl's phenomenological approach. Data collection includes non-structural interviews with participatory observation and non-intervention strategies, documentation is then analyzed using data reduction techniques, data presentation, interpretation, drawing conclusions. The results of the study show (1) the strategy of empowering the Fatimah Azzarah fishing women's group (KWN) is by instilling awareness of their roles and identities that are able to contribute to the economy of their families and after this awareness is formed, the fishing women's groups (KWN) are given knowledge and training in managing marine products to be able to do business and compete in the food industry. (2) The inhibiting factor in empowering women from the Fatimah Azzarah fishermen women's group is that there is still an unequal distribution of fishing gear for husbands and wives of the Fatimah Azzarah fishermen women's group (KWN) so that it has an impact on the economic income of the family and with it the Fatimah fishermen women's group (KWN). Azzarah overcomes this by promoting their processed products in social media space and also the inhibiting factor is the lack of community participation in empowering women, the Fatimah Azzarah fishing women's group (KWN) overcomes them by developing informal advocacy programs and paralegal work, including assistance for victims of violence in households, girls' schools and schools are confident that the community will participate in this empowerment which does not only focus on the economic benefits of the Fatimah Azzara fishermen women's group (KWN) but covers the community at a macro level.